Professional foreign-language training of future teachers of technical disciplines - Zelenin , H. (Problems of Engineer-Pedagogical Education, 2021)
The article deals with the necessity to enhance the quality of professional foreign-language training of future teachers of technical disciplines, based on the process of internationalization of higher technical education and integration of technical universities into the global scientific and educational community. The author gives the definition of professional-communicative competence, defines conditions that are necessary for realization of professional foreign-language training of future teachers of technical disciplines. The author highlights, that a professionally-oriented approach to foreign language teaching in technical universities, focused on the students' ability development to communicate in a foreign language in specific professional, business, scientific fields and situations, considering the peculiarities of professional thinking, when organizing a motivational-incentive and research activities. The article emphasizes the importance of designing the training program content with the use of professional context by means of modelling the forms, conditions and content of future teachers’ of technical disciplines professional activities; describes the means that are used to create for learning purposes the subject and social content of future teachers’ of technical disciplines professional activities; puts a special accent on the role of problematic -communicative tasks, namely, case studies related to future teachers’ of technical disciplines professional activities that have to be solved by means of a foreign language. As the author puts it, solving problematic-communicative tasks involves learners into a highly-motivated language behavior and allows for acquiring new language knowledge and communicative skills, gradually transforming cognitive motivation into professional one related to practical use of a foreign language in future teachers’ of technical disciplines professional activities. It results in forming practical skills of all kinds of speech activity. The author emphasizes that the future teachers of technical disciplines training in the context of the communicative-cognitive approach is determined by a qualitative change in modern requirements for the educational process organization and provides for the obligatory consideration of the cognitive preferences and psychophysiological status of students, aimed at their holistic understanding development of a foreign language system as well as the ability for practical communication